(untitled) (Fiep Bulletin - online, 2016)
The bag has been used a long time as a method of transporting school supplies for students at different ages. It is known that overweight found in the backpacks and improperly transport is one of multifactor providing changes and pain in the spine, the load of the backpack when over 10% of body mass contributes to postural deviations and pains, taking into consideration that school every day carry the weight of material on the shoulders to that over the years this weight increases as the curriculum is essential care to overweight in order to prevent irreversible damage to spine. Taking into consideration the importance of public health policies in school this study was to evaluate the mode of transport and overhead school supplies in backpacks carried by children during their school years, sought to be identified children carry the weight of the backpacks close to 10% of body weight which is recommended by WHO and described in Law No. 9507/2004 Municipal and State Law No. 12,027 / 2003. A cross-sectional observational analytical and descriptive methodology was used to analyze the weight of the backpack of students in elementary school to two state schools in the Northern District of Porto Alegre. The sample consisted of 157 students from 1st to 5th grade elementary school where it was found that 78% of students carry their stuff in two backpack straps, 15% carry in backpacks on wheels and only the students of 1st and 2nd year use the training wheels creeping form puts the rest back and 8% choose to use grants, 75% of the students carry the appropriate weight within 10% provided by law and 25% exceed the estimated weight. We conclude therefore that students carry on weight during their school life.